Scaling up research-for-development innovations in food and agricultural systems. Issue 6 (18th August 2019) - Shilomboleni, Helena; De Plaen, Renaud
ABSTRACT: The last decade has seen a growing interest in scaling up innovations to realise wider benefits from development investments. While numerous proven technologies, products and models have been successfully piloted, scaling them up through expansion, adoption and replication has proved challenging, particularly in poor regions of the world. The low uptake of innovations is partially attributed to the design of technologies, in a manner that is not compatible with local farming practices. At the same time, proven innovations fail to generate large impacts at scale because implementing actors have not sufficiently understood or effectively engaged with the scaling process. This article shares lessons from the Canadian International Food Security Research Fund (CIFSRF) that supported applied research to develop, test and scale up promising food and nutrition security innovations. Key lessons include ensuring that innovations are embedded within local socio-ecological systems; engaging end users throughout the research process and enabling participatory decision-making; and considering the investment returns of innovations for end-users.